Allah sebagai Ibu bagi Semua yang Berdosa - Elis Timang; Agustinus Ruben (LPPM STT Baptis Kalvari, 2024)
The image of God as Mother in the Bible is a very interesting topic to be studied in depth. In the patriarchal context of the Bible, the image that is often used in understanding God is “Father.” God is always referred to as Father, even in His role as Father to His children, not Mother. This view has quite an impact on the way believers view God today, who see God as Father, and are known and addressed only as Father. For this reason, this study aims to explore the revelation of God's maternal side through the narrative of Genesis Chapter 3:1-24, which departs from a feminist perspective to see God from a Motherly perspective. Using a biblical studies approach and hermeneutical text analysis, this study seeks to reveal the image of God as Mother, as well as its implications for theological understanding in the contemporary context. Through in-depth analysis, this study identifies several elements that reflect God's motherhood, including God's great love and care for humans, the discipline and rebuke given, and the promise and hope offered. This image of God as a Mother provides a new perspective in understanding the character and nature of God who is not only a Father, but also a Mother who is compassionate, disciplining, and full of mercy and forgiveness.